2022
DOI: 10.1007/s11682-022-00693-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cardiorespiratory fitness and exercise with brain white matter in healthy adults: A systematic review and meta-analysis

Abstract: Magnetic resonance imaging (MRI) studies have revealed positive associations between brain structure and physical activity, cardiorespiratory fitness, and exercise (referred to here as PACE). While a considerable body of research has investigated the effects of PACE on grey matter, much less is known about effects on white matter (WM). Hence, we conducted a systematic review of peer-reviewed literature published prior to 5th July 2021 using online databases (PubMed and Scopus) and PRISMA guidelines to synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…The only longitudinal study where the authors considered this relationship showed no relation between favorable changes in cardiorespiratory fitness evoked by intense aerobic exercise and myelin expansion (Mendez Colmenares et al, 2021). This finding is somewhat contradictory to the belief that exercise-induced changes in cardiovascular performance represent a key element in cognitive improvement (Aczel et al, 2022;Maleki et al, 2022;Renke et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…The only longitudinal study where the authors considered this relationship showed no relation between favorable changes in cardiorespiratory fitness evoked by intense aerobic exercise and myelin expansion (Mendez Colmenares et al, 2021). This finding is somewhat contradictory to the belief that exercise-induced changes in cardiovascular performance represent a key element in cognitive improvement (Aczel et al, 2022;Maleki et al, 2022;Renke et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies indicate that relatively higher global white matter volumes may be related to higher levels of physical activity and fitness. 68,69 The cerebellum is crucially involved in movement control, as well as a number of other cognitive functions. 70 It is clearly possible that shorter sleep times may lead to relatively higher levels of physical activity due to more time spent awake, which may in turn be linked to higher global and cerebellar white matter volumes.…”
Section: Discussionmentioning
confidence: 99%
“… 54 57 For example, a recent meta-analysis described correlation between physical activity, cardiorespiratory fitness, and exercise and microstructural integrity of the corpus callosum, and the anterior limb of internal capsule, with effect sizes of 0.345 and 0.198, respectively. 55 Another meta-analysis found that increased obesity measurements were related to reduced FA in the genu of the corpus callosum. 57 A meta-analysis of white matter correlates of relatives of patients with severe mental disorders (MDD, bipolar disorder, and/or schizophrenia) showed decreased FA in the genu and splenium of the corpus callosum in relatives of patients as compared to controls, although a specific effect size was not reported.…”
Section: Discussionmentioning
confidence: 99%